ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR GUGUS 3 KECAMATAN JALAKSANA KABUPATEN KUNINGAN - Cahya Utami, Maulidya; Nanan Abdul Manan (Universitas Muhammadiyah Kuningan, 2024)
The implementation of the independent curriculum has been implemented in schools in Indonesia in the 2022/2023 school year. What are the perceptions of teachers in implementing the independent curriculum, what are the conditions of infrastructure in implementing the independent curriculum, and how the implementation of the independent curriculum is interesting to study. The method used in this research is descriptive qualitative. This research was collected through interviews, observations and documentation. The results of this study are that elementary schools in cluster 3 of Jalaksana District, Kuningan Regency have implemented an independent curriculum in terms of P5 learning. The obstacles to implementing the practice of strengthening the Pancasila student profile (P5) are incomplete infrastructure and lack of teacher understanding of the independent curriculum due to lack of training. The obstacles that arise are trying to be overcome with various kinds of learning media and only rely on the independent teaching platform provided by the Ministry of Education and guided by the driving teacher.